FORMATION OF CREATIVE PERSONALITY OF A FUTURE TEACHER BY MEANS OF COMMUNICATIVE-CREATIVE APPROACH TO TEACHING HUMANITIES IN CHILDREN’S CHILDREN - Reshetnikova, H.B. (Pedagogy of Higher and Secondary Education, 2010)
In this article the formation of creative personality of future teacher by means of communicatively-creative approach in the process of teaching of human disciplines is considered.